Light-induced changes of the subretinal space of the temporal retina observed via optical coherence tomography - Messner, Alina (2020)
Photoreceptor function is impaired in many retinal diseases like age-related macular degeneration. Currently, assessment of the photoreceptor function for the early diagnosis and monitoring of these diseases is either subjective, as in visual field testing, requires contact with the eye, like in electroretinography, or relies on research prototypes with acquisition speeds unattained by conventional imaging systems. We developed an objective, noncontact method to monitor photoreceptor function using a standard optical coherence tomography system. This method can be used with various white light sources for stimulation. The technique was applied in five volunteers and detected a decrease of volume of the subretinal space associated with light adaptation processes of the retina.